Paraneoplastic dermatomyositis associated with urothelial cancer: report of a case and systematic review of the literature - Sabaté-Ortega, Josep; Bujons-Buscarons, Elisabet; Fina-Planas, Clàudia; Vilanova-Anducas, Núria; Vidal-Sarró, Noemí; Sala-González, Núria (Frontiers in Oncology, 2023)
The idiopathic inflammatory myopathies (IIM) are a collection of autoimmune diseases that have a substantial impact on the entire body and include conditions such as dermatomyositis (DM), polymyositis (PM), sporadic inclusion body myositis, and immune-mediated necrotizing myopathy. These disorders are characterized by symptoms such as muscular weakness, pain, and dermal rash. This systematic review is intended to explore the potential link between bladder cancer and DM/PM.We performed a comprehensive systematic search on PubMed and Scopus until August 2022 to identify relevant research studies. The studies that met our inclusion criteria focused on patients with urinary bladder cancer and dermatomyositis, and/or polymyositis.The patients' median age was 65.5 years (47-79), with the majority being male (15, 39.47%).Bladder cancer manifested before PM/DM in 5 (13.15%) patients, while in the majority of cases occurred after the cancer diagnosis. The stage of cancer at the time of the initial PM/DM diagnosis were mostly locally (11/20, 50%).During the first presentation, the patients had a median creatine kinase level of 2227 U/L, ranging between 44 and 10471. In one case, anti-TIF-1γ antibodies were found to be present. Among the cases with reported medical history (20/38), treatment immediately improved DM symptoms in 16 patients(53.8%) and in 3 patients(15%), symptoms of DM resurfaced during the period after the operation.Death was reported in 14 (36.8%) patients.In conclusion, our study provides knowledge and understanding for identifying specific risk factors in patients with the coexistence of bladder cancer and DM/PM and their management. During the initial and follow-up screening, age, gender, and the clinicopathological subgroup of myositis should be considered to ensure proper management of the condition.